In vitro sustained release study of gallic acid coated with magnetite-PEG and magnetite-PVA for drug delivery system - Dorniani, Dena; Kura, Aminu Umar; Hussein-Al-Ali, Samer Hasan; Hussein, Mohd Zobir; Fakurazi, Sharida; Shaari, Abdul Halim; Ahmad, Zalinah (Hindawi Publishing Corporation, 2014)
The efficacy of two nanocarriers polyethylene glycol and polyvinyl alcohol magnetic nanoparticles coated with gallic acid (GA) was accomplished via X-ray diffraction, infrared spectroscopy, magnetic measurements, thermal analysis, and TEM. X-ray diffraction and TEM results showed that Fe3O4 nanoparticles were pure iron oxide having spherical shape with the average diameter of 9 nm, compared with 31 nm and 35 nm after coating with polyethylene glycol-GA (FPEGG) and polyvinyl alcohol-GA (FPVAG), respectively. Thermogravimetric analyses proved that after coating the thermal stability was markedly enhanced. Magnetic measurements and Fourier transform infrared (FTIR) revealed that superparamagnetic iron oxide nanoparticles could be successfully coated with two polymers (PEG and PVA) and gallic acid as an active drug. Release behavior of gallic acid from two nanocomposites showed that FPEGG and FPVAG nanocomposites were found to be sustained and governed by pseudo-second-order kinetics. Anticancer activity of the two nanocomposites shows that the FPEGG demonstrated higher anticancer effect on the breast cancer cell lines in almost all concentrations tested compared to FPVAG.